Das Europäische Raumentwicklungskonzept als Grundlage für grenzüberschreitende Kooperationen - Zimmermann, Friedrich M. (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1999)
This is a report on goals and projected strategies of The European Concept of Spatial Development (EUREK) which was launched in Brussels, in 1999. The author points out selected visions of the programme and calls for a concentrated action of the candidates to join the European Union and the member states themselves to develop several transborder cooperations projects.The complementarity in the border regions and the planning of such developments across borders will be supported by the EUREK itself.
Keywords: Europe; European Union; Evropa; Evropska unija; mednarodni odnosi; obmejna območja; obmejno sodelovanje; politična geografija; prostorski razvoj; regije